2017
DOI: 10.1093/mnras/stx2196
|View full text |Cite
|
Sign up to set email alerts
|

Medium-resolution near-infrared spectroscopy of massive young stellar objects

Abstract: We present medium-resolution (R∼7000) near-infrared echelle spectroscopic data for 36 MYSOs drawn from the Red MSX Source (RMS) survey. This is the largest sample observed at this resolution at these wavelengths of MYSOs to date. The spectra are characterized mostly by emission from hydrogen recombination lines and accretion diagnostic lines. One MYSO shows photospheric HI absorption, a comparison with spectral standards indicates that the star is an A type star with a low surface gravity, implying that the MY… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 56 publications
7
33
2
Order By: Relevance
“…However, Simon et al (1983) showed that winds of MYSOs can be so dense that hydrogen is collisionally excited to its n=2 state, which makes its ionisation from cooler stars possible (see also, Koumpia et al 2020;Drew et al 1998;Drew 1998). Indeed, a bloated star could also explain the narrow single line profiles of Brγ observed in MYSOs in various studies (e.g., Pomohaci et al 2017), which is in contrast to the relatively broader and double-peaked lines predicted by disc models around hot main sequence stars (Sim et al 2005). Indeed, a slightly bloated object would have a larger disc (inner) radius and thus lower rotational velocities (i.e., narrow line profiles).…”
Section: Origin Of the Brγ Emissionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, Simon et al (1983) showed that winds of MYSOs can be so dense that hydrogen is collisionally excited to its n=2 state, which makes its ionisation from cooler stars possible (see also, Koumpia et al 2020;Drew et al 1998;Drew 1998). Indeed, a bloated star could also explain the narrow single line profiles of Brγ observed in MYSOs in various studies (e.g., Pomohaci et al 2017), which is in contrast to the relatively broader and double-peaked lines predicted by disc models around hot main sequence stars (Sim et al 2005). Indeed, a slightly bloated object would have a larger disc (inner) radius and thus lower rotational velocities (i.e., narrow line profiles).…”
Section: Origin Of the Brγ Emissionmentioning
confidence: 87%
“…The origin of the Brγ emission observed in the close vicinity of (M)YSOs (Mendigutía et al 2011;Murakawa et al 2013;Davies et al 2010;Kraus et al 2008;Pomohaci et al 2017;Lumsden et al 2012) can be explained by theory (e.g., jets, magnetospheric accretion, disc wind; Ferreira 1997;Tambovtseva et al 2014Tambovtseva et al , 2016 and can be further tested by observationally constraining the spatial origin of the emission compared to the size of the hot dust (2.2 µm emission). The GRAVITY dataset allows us to estimate the size of the ionised gas by measuring visibilities at the central spectral channel of the Brγ emission towards 4 MYSOs and directly compare it to that of the continuum emission.…”
Section: Brγ Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently this has been achieved for the first time. The MYSO G015.1288-00.6717 shows an A-type spectrum with a relatively low surface gravity, pointing to a bloated protostar (Pomohaci et al 2017).…”
Section: Uncertainty Of the Accretion Parametersmentioning
confidence: 99%
“…High-mass young objects tend to have a larger fraction of CO detections than lower luminosity ones. Most recently, Pomohaci et al (2017) detected the CO overtone emission in a subset of 7 out of 38 massive young stellar objects (MYSO). These detections seem to be confined to a narrow range ofṀ acc (10 −4.5 -10 −3.0 M yr −1 ), where they account for about 40% of the objects.…”
Section: Discussionmentioning
confidence: 99%